Development of a Pulse Shape Discrimination Algorithm - Wood, Jack (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.Pulse Shape Discrimination is the process of distinguishing between radiation types such as neutrons or gamma-rays. Dual detector scintillators can be used as they fluoresce from both neutron and gamma interactions. Once the light has been collected on the photo sensor and its electric signal gets digitised, discrimination algorithms can be applied to identify the radiation type on a event-by-event basis. Several types of algorithms exist, each with benefits and disadvantages. Several algorithms and filters have been built and are currently being tested on temperature data from a summer project. The resultant codes form the framework of a novel algorithm which is currently being developed. Experimental data has also been recorded to begin building the pulse shape database required for the novel algorithm and to test the discrimination algorithms.
Keywords: 'Pulse shape discrimination'; 'Neutron/Gamma'; 'DSDS18 poster'; 'DSDS18'; 'Radiation and Matter'